Album aangeboden aan Van Rantwijk t.g.v. zijn afscheid als algemeen secretaris van de NVJ 1947-1972
Album aangeboden aan Van Rantwijk t.g.v. zijn afscheid als algemeen secretaris van de NVJ 1947-1972.